2020
DOI: 10.1530/eje-20-0350
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic autoimmune thyroiditis are not at higher risk for developing clinically overt thyroid cancer: a 10-year follow-up study

Abstract: Objective The association between chronic autoimmune thyroiditis (CAT) and differentiated thyroid cancer (DTC) remains controversial. The incidence of DTC increases when screening procedures are implemented, as typically occurs in CAT patients being routinely submitted to thyroid Ultrasound (US). The aim of this study was to longitudinally evaluate the long-term development of DTC in patients with CAT. Design and Methods A retrospective longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Also, they were more recently reassessed in several studies conducted in consecutive patients submitted to FNA, who are believed to be less subject to potential selection bias of surgical series [35]. However, according to FNA studies, the link between PTC and HT seems less evident [18,46] Rotondi et al [19] in a 10 year follow-up study of 510 patients with CAT, who presented a negligible risk of developing thyroid carcinoma nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they were more recently reassessed in several studies conducted in consecutive patients submitted to FNA, who are believed to be less subject to potential selection bias of surgical series [35]. However, according to FNA studies, the link between PTC and HT seems less evident [18,46] Rotondi et al [19] in a 10 year follow-up study of 510 patients with CAT, who presented a negligible risk of developing thyroid carcinoma nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports describe a higher prevalence of benign nodules in HTthan in the general population, which is usually attributed to stimulating factors such as TSH, IGF1, and local cytokines. However, there is still controversy whether CAT predisposes to malignancy [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune thyroiditis, also known as Hashimoto thyroiditis, was first considered as a risk factor for PTC in 1955 [ 7 ], along with a family history of PTC [ 8 ], therapeutic and diagnostic irradiation [ 5 ], and inadequate dietary intake of iodine [ 9 ]. After the initial 1955 report [ 7 ], several studies have examined the PTC-thyroiditis association (summarized in Table 1 ), especially after the introduction of cancer immunotherapy to the clinical practice [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Autoimmune Thyroiditis and Papillary Thyroid Cancer: New Ins...mentioning
confidence: 99%
“…Scholars have long debated whether this association represents the coexistence of two independent but common diseases that are brought together by the increased use of thyroid ultrasound and fine-needle aspiration, or if it instead reflects a true cause–effect relationship [ 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some studies have suggested that thyroiditis attenuates PTC severity [ 12 , 13 , 20 , 24 , 25 , 29 , 30 , 31 ], while others have concluded that thyroiditis promotes the progression of PTC [ 10 , 17 , 18 , 19 , 32 ]. Recently, McLeod et al [ 32 ] conducted a case-control study nested within the United States Army personnel who served between 1996 and 2014.…”
Section: Autoimmune Thyroiditis and Papillary Thyroid Cancer: New Ins...mentioning
confidence: 99%
“…Consistent with this, some studies show that HT and the occurrence of thyroid cancer have a strong correlation ( 10 , 11 ). Unlike this, several studies indicate that HT is not associated with the development of thyroid cancer and breast cancer ( 12 , 13 ). Given conflicting evidence and newly added epidemiological studies, we conducted a meta-study to examine and assess the association between HT and cancer.…”
Section: Introductionmentioning
confidence: 96%